Salivary cortisol levels: the importance of clown doctors to reduce stress - Saliba, Flavia G. [UNESP]; Adiwardana, Natanael S. [UNESP]; Uehara, Eliane U. [UNESP]; Silvestre, Renata N. [UNESP]; Leite, Victor V. [UNESP]; Faleiros, Francisca T. V. [UNESP]; Padovani, Flavia H. P. [UNESP]; De Gobbi, Juliana I. F. [UNESP] (Pagepress Publ, 2016)
This study was designed to correlate entertainment of clown-doctors (CD) activities on hospitalized children and aphysiological biomarker. For this purpose we collected saliva samples and verified children satisfaction with these activities by using a visual analog scale (VAS). Children from 6 to 7 years-old, with diagnosis of any acute pathology, interned in the Pediatric Ward of the Botucatu Medical School Hospital (Sao Paulo. Brazil) were interviewed. Two groups were taken into consideration: lunchCD and dinnerCD. The following protocol was applied in each group (lunch and dinner): collection of the first saliva sample and presentation of VAS prior to CD activities, followed by collection of a second saliva sample and another VAS assessment after CD activities. The salivary cortisol was reduced in both groups comparing the first saliva sample. The satisfaction of the intervention was evident for lunchCD. The CD intervention is effective in decreasing an important physiological biomarker of stress factor, cortisol, in hospitalized children, been effective for the healing process.
Keywords: Salivary cortisol; downs doctors; biomarker of stress; visual analog scale